Review Article : Daun Jamblang (Syzygium cumini L.) Digunakan Sebagai obat - Himyatul Hidayah; Refriyanti Irma; Tasya Putri Pratiwi; Elista Indah Susanti (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Jamblang (Syzigium cumini L) is a plant that almost all parts of the plant have many benefits including the leaves. Jamblang leaves contain compounds such as flavonoids, antioxidants, alkaloids, tannins, quercetin, myricetin, kaempferol, polyphenols, quinones, Lupeol, 12-oleanen-3-ol-3β-acetate, Stigmasterol, ß-sitosterol, terenoid, ß-sitosterol, Betulinic. acid, flavonol which has medicinal properties. This study aims to determine the usefulness or efficacy of jamblang leaves as medicine. This research method uses the type of Literature Review Article research with database results taken from various articles via Google Scholar, Sciendirect, and Pubmed. The results of various studies show that jamblang leaves have medicinal properties as antioxidants, anti-diarrhea, antimicrobial, anti-fungal, antihyperuremic, cariovascular, larvicidal and anti-inflammatory.